Akibat Hukum Perjanjian Jual Beli Tanah di Bawah Tangan dalam Perspektif Hukum Perdata dan Hukum Pertanahan - Yulius Efendi (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2026)
Land sale and purchase agreements are legal acts frequently carried out in social practice. However, such agreements are often executed under hand without the involvement of authorized officials as required under land law. The practice of under-hand land sale and purchase gives rise to various legal issues, particularly concerning the validity of the agreement, the transfer of land rights, and legal protection for the parties in the event of disputes. This article aims to analyze the legal status of under-hand land sale and purchase agreements from the perspectives of civil law and land law, examine the legal consequences arising from such agreements on the transfer of land rights, and review the forms of legal protection available to the parties. The research method employed is normative juridical, using statutory and conceptual approaches. The findings indicate that under-hand land sale and purchase agreements may be considered valid under civil law as long as they fulfill the legal requirements of a valid agreement; however, they do not automatically result in the transfer of land rights under land law. Consequently, the legal position of the buyer becomes weak in the event of a dispute. Therefore, public legal awareness and the role of the state in strengthening dissemination and enforcement of land law are necessary to ensure legal certainty and protection.